2016
DOI: 10.1016/j.bpj.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Voltage Activation of Cortical KCNQ Channels Depends on Global PIP2 Levels

Abstract: The slow afterhyperpolarization (sAHP) is a calcium-activated potassium conductance with critical roles in multiple physiological processes. Pharmacological and genetic data suggest that KCNQ channels partly mediate the sAHP. However, these channels are not typically open within the observed voltage range of the sAHP. Recent work has shown that the sAHP is gated by increased PIP2 levels, which are generated downstream of calcium binding by neuronal calcium sensors such as hippocalcin. Here, we examined whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 45 publications
4
45
1
Order By: Relevance
“…The present observation that increasing cellular PIP 2 levels with PIP5K negatively shifted the V ½ of Kv7.2 channels (as previously described for Kv7.159, Kv7.249, and other heteromeric Kv7 channels31) and decreased retigabine-induced responses in both in Kv7.2 and Kv7.2 R325G channels, indicates that retigabine and PIP 2 act via at least partially overlapping mechanisms to stabilize voltage-dependent pore opening; consistent with this view is the fact that PIP 2 -depleted Kv7.3 channels are insensitive to retigabine60.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present observation that increasing cellular PIP 2 levels with PIP5K negatively shifted the V ½ of Kv7.2 channels (as previously described for Kv7.159, Kv7.249, and other heteromeric Kv7 channels31) and decreased retigabine-induced responses in both in Kv7.2 and Kv7.2 R325G channels, indicates that retigabine and PIP 2 act via at least partially overlapping mechanisms to stabilize voltage-dependent pore opening; consistent with this view is the fact that PIP 2 -depleted Kv7.3 channels are insensitive to retigabine60.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the present results add severe forms of Kv7.2-related epilepsy to the growing list of channelopathies caused by changes in PIP 2 -dependent regulation159; the recent observation that Kv7 channels are critical determinants of the cortical excitability changes occurring upon dynamic regulation of PIP 2 levels31, lends further support to the pathogenetic role of the proposed mechanism in individuals carrying the Kv7.2 R325G variant. Future studies will further explore the structural implications of the functional results herein presented, and define whether such specific molecular defect is associated with distinct clinical features.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While it has been known that PIP 2 interaction with Kv7 is mandatory for channel function [34,35], more recently it was shown that PIP 2 has multiple sites of interaction within the channel, with varying effects [36]. One such PIP 2 interaction modulates coupling the voltage-sensing to the pore-gating domain [3740]. Functionally, PIP 2 interaction within the voltage-sensing domain of the S4-S5 linker has been attributed to increasing open probability thus voltage-conductance [40].…”
Section: Components Of the Kv7 Channel Complexmentioning
confidence: 99%
“…However, BACE1 did not alter the decrease of KCNQ2/3 currents upon PIP 2 depletion, nor did PIP 2 displace BACE1. 96,103 Thus, BACE1 appears to act differently than KCNE1, which sensitizes KCNQ1 to PIP 2 . 104 Furthermore, the currentpromoting effect of BACE1 was different from that of the established M-current activator retigabine.…”
Section: Direct Interaction and Kcnq Gatingmentioning
confidence: 99%